Avaliação neuropsicológica das funções cognitivas de pessoas idosas em processo de interação no ciberespaço - Kieling, Mônica Luísa (2017)
Technologies are evolving more and more, and being used for different purposes, one is in the interaction between people in cyberspace, information and communication technologies can stimulate cognitive functions, emotions, and social interaction; and social networks serve as a gateway to working with the elderly persons the benefits that technology brings. The research carried out consisted in evaluating the emotions and the emotional regulation raised in the participants of the research and also to evaluate the neuropsychological functions of memory, language, executive functions and practices, raised before andafter the interaction process in a social network. In this paper we present the secondary objective of production I, which was to evaluate the neuropsychological functions of attention, memory and praxis, pre and post intervention. The research is a randomized, interventional and descriptive-analytical clinical type. The sample consisted of 41 elderly women, aged between 62 and 76 years old, participating in groups of coexistence of the Coordination of Attention to the Elderly of Passo Fundo/RS. The members were randomly divided into two intervention groups in cyberspace, with and without emotional motivation, and a control group, the intervention consisted of working in computer workshops and the social network chosen was Facebook, the research was conducted in a period of 4 months, with a total of 15 meetings, once a week. Pre- and post-intervention neuropsychological evaluation was performed with the Neupsilin Brief Neuropsychological Assessment Instrument, in a period of 5 months interval. As a result, the research showed a significant improvement in the cognitive functions of attention and memory in the intervention groups and deficits in the control group. The data was analyzed using the KruskalWallis test, the level of significance used in the tests was p ≤ 0.05.